(untitled) (Archives of Pediatrics of Uruguay, 2022)
Introduction: congenital anomalies (CA) are a public health problem with an impact on childhood, infant mortality (IM) and disability. In Uruguay, as well as in other developed countries, CA and prematurity are the main causes of IM. Objectives: analyze the most frequent anomalies in the country in 2011-2014 and evaluate risk factors. Material and methods: the data were obtained from the National Record of Congenital Defects and Rare Diseases and health statistics from the Ministry of Public Health. Results: it was determined that practically half of the cases were: congenital heart disease, Down syndrome and Neural Tube Defects (anencephaly, encephalocele and myelomeningocele), accounting for 0.42% (812/191,820) and 2.85% (38/1334) of live births and stillbirths respectively. The prevalence per 10,000 NV and stillbirths were: 38.52 and 149.93 for Congenital Heart Disease; 3.6 and 7.5 for Down Syndrome; 2.1 and 127.4 for neural tube defects. Advanced maternal age was the main risk factor for Down syndrome. The risk factors observed in the three selected anomalies were: prematurity, neonatal depression and low birth weight. Conclusions: congenital anomalies in general, and those selected in this study in particular, are a relevant cause of morbidity and mortality in newborns and infants, likely to be prevented. Early diagnosis is essential for planning specialized health services. The results presented in the present paper can be used as a baseline to measure the impact of health actions at national level.